2007
DOI: 10.1103/physrevlett.99.197001
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Electron Relaxation in SuperconductingBi2Sr2CaCu2O8+δby Time-Resolved Photoelectron Spectroscopy

Abstract: Time-resolved photoelectron spectroscopy is employed to study the dynamics of photoexcited electrons in optimally doped Bi{2}Sr{2}CaCu{2}O{8+delta} (Bi-2212). Hot electrons thermalize in less than 50 fs and dissipate their energy on two distinct time scales (110 fs and 2 ps). These are attributed to the generation and subsequent decay of nonequilibrium phonons, respectively. We conclude that 20% of the total lattice modes dominate the coupling strength and estimate the second momentum of the Eliashberg couplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

33
401
4
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 324 publications
(439 citation statements)
references
References 28 publications
33
401
4
1
Order By: Relevance
“…[1][2] Time-resolved spectroscopy with ultrafast temporal resolution is a complementary tool to investigate the temporal evolution of the QP-bosonic degrees of freedom [3][4][5][6][7][8] that is capable to disentangle the contribution of bosonic excitations from the dynamics viewpoint. 6 Based on this observation, the non-equilibrium optical spectroscopy has been extensively applied to explore mechanisms of phase separation, [9][10][11][12][13][14][15] boson pairing, 16 and the electron-phonon coupling [17][18][19][20][21] in superconductors by monitoring the QP dynamics; the experimental results are conventionally connected to microscopic processes by application of a phenomenological model proposed by Rothwarf and Taylor (i.e. the RT model).…”
mentioning
confidence: 99%
“…[1][2] Time-resolved spectroscopy with ultrafast temporal resolution is a complementary tool to investigate the temporal evolution of the QP-bosonic degrees of freedom [3][4][5][6][7][8] that is capable to disentangle the contribution of bosonic excitations from the dynamics viewpoint. 6 Based on this observation, the non-equilibrium optical spectroscopy has been extensively applied to explore mechanisms of phase separation, [9][10][11][12][13][14][15] boson pairing, 16 and the electron-phonon coupling [17][18][19][20][21] in superconductors by monitoring the QP dynamics; the experimental results are conventionally connected to microscopic processes by application of a phenomenological model proposed by Rothwarf and Taylor (i.e. the RT model).…”
mentioning
confidence: 99%
“…These techniques aim to study the recombination of photoexcited quasiparticles and the resulting recovery of the superconducting condensate. In HTSCs, timeresolved (TR) angle-resolved photoemission spectroscopy 16 and TR optical reflectivity 17 have indicated that the excited quasiparticles preferentially couple to a small number of phonon subsets before decaying through anharmonic coupling to all other lattice vibrations, in support of the notion that selective optical phonon modes give rise to anisotropy of the electron-phonon (el-ph) coupling. 3 In addition, this anisotropy has also been observed in TR electron diffraction, 18 while resonant femtosecond study of both electronic and phononic degrees of freedom suggests strong el-ph coupling.…”
Section: Introductionmentioning
confidence: 95%
“…The model phenomenologically includes the effect of the pump pulse but addresses in greater depth the electron-hot phonon coupling based on a microscopic model Hamiltonian for dwave superconductivity in HTSCs. This microscopic treatment goes beyond previous effective models for the normal state, 16,27 allowing us to describe the quasiparticle dynamics in both the normal and superconducting states with the same approach. Within this unified model, the time evolution of the whole set of experimental measurables can be calculated in a streamlined way.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, this techniques has been successfully carried into the time domain by applying various pump-probe schemes with femtosecond time resolution. Simultaneous acquisition of spectral and dynamic information about the out-of-equilibrium carrier excitation and relaxation processes at selected momenta in the Brillouin zone is thereby made possible, opening unprecedented opportunities for understanding the ultrafast transient changes in the charge ordered states in charge density wave materials [1][2][3], the time-scale for the interaction between electrons and bosonic particles in high-temperature superconductors [4,5] and the dynamics taking place on the Dirac cone in graphene [6,7].…”
Section: Angle-resolved Photoemission Spectroscopy (Arpes) Is a Well-mentioning
confidence: 99%